2019
DOI: 10.1002/anie.201907797
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Tertiary Amine/Chiral Iridium Complex Catalyzed Asymmetric [4+3] and [3+3] Annulation Reactions

Abstract: Asymmetric reactions merging organocatalysis and metal catalysis significantly broaden the scope of organic synthesis.N evertheless,t he accomplishment of stereoselective annulations combining two types of dipole species,i ndependently generated from the activations of organocatalysts and metal complexes,s till remains as ac hallenging task. Now, Morita-Baylis-Hillman carbonates from isatins and carbamate-functionalized allyl carbonates could be chemoselectively activated by achiral Lewis basic tertiary amines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(24 citation statements)
references
References 87 publications
0
24
0
Order By: Relevance
“…Subsequently, the same authors reported the asymmetric [4+3] annulation between isatin-derived MBH carbonates 157 and carbamate-functionalised allylic carbonates 158 for the synthesis of spirooxindoles 160 under tertiary amine/chiral iridium-complex dual catalysis (Scheme 22A). 58 The nucleophilic ylide intermediate 161, generated between DABCO and the MBH carbonate 157, undergoes regioselective -allylation with the chiral -allyliridium complex 162. Subsequently, cyclisation of intermediate 163 through intramolecular aza-Michael addition and -elimination of the Lewis base affords the seven-membered annulated products 160 in good yields and excellent diastereo-and enantiocontrol.…”
Section: Mbh Adduct As Nucleophilementioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the same authors reported the asymmetric [4+3] annulation between isatin-derived MBH carbonates 157 and carbamate-functionalised allylic carbonates 158 for the synthesis of spirooxindoles 160 under tertiary amine/chiral iridium-complex dual catalysis (Scheme 22A). 58 The nucleophilic ylide intermediate 161, generated between DABCO and the MBH carbonate 157, undergoes regioselective -allylation with the chiral -allyliridium complex 162. Subsequently, cyclisation of intermediate 163 through intramolecular aza-Michael addition and -elimination of the Lewis base affords the seven-membered annulated products 160 in good yields and excellent diastereo-and enantiocontrol.…”
Section: Mbh Adduct As Nucleophilementioning
confidence: 99%
“…Further, the authors expanded this Lewis base/iridium-complex dual catalytic approach to the asymmetric [3+3] annulation between MBH carbonates and vinyl N-Ts aziridines (not shown). 58 Soon after, Li, Duan and co-workers reported a closely related process under phosphine/palladium dual catalysis for the [4+3] annulation between MBH carbonates 164 and vinylbenzoxazinanones 165 (Scheme 22B). 59 In agreement with Chen's work, 57 the dissociated PPh 3 from the palladium complex is enough to activate the MBH carbonate 164 generating the corresponding nucleophilic P-ylide intermediate.…”
Section: Mbh Adduct As Nucleophilementioning
confidence: 99%
“…One of the most recent examples comes from the groups of Du and Chen, who have demonstrated that the dual-catalyst system of an Ir-catalyst and 1,4-diazabicyclo [2.2.2]octane (DABCO) can be used to generate enantioenriched spirocyclic oxindoles 6.1e from Morita-Baylis-Hillman (MBH) carbonates 6.1a and allylic carbonates 6.1b (Scheme 6.1). 65 During the optimization of the reaction, the authors found that a chiral Lewis base could be used to react with the 6.1a as well as coordinate to the Ir(cod)Cl 2 catalyst to give up to 50% ee. The enantioselectivity of the reaction greatly improved when the Ir-catalyst was pre-complexed to the chiral ligand.…”
Section: H Lam M Lautensmentioning
confidence: 99%
“…Finally, this protocol enabled an efficient synthesis of the core of a potent MDM2 inhibitor. Most recently, Du and Chen used cooperative iridium/tertiary amine catalysis to enable formal [4+3] cycloaddition reactions between two different allyl carbonate substrates [37]. This was possible via catalyst-selective substrate activation; the Morita-Baylis-Hillman (MBH) carbonates are selectively activated by the tertiary amine Lewis base catalyst, whereas the allylic t-butylcarbonate is selectively activated by the iridium catalyst (Scheme 29).…”
Section: Cooperative Tertiary Amine Lewis Base/iridium Catalysismentioning
confidence: 99%